2010
DOI: 10.1111/j.1744-9987.2010.00860.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiothoracic Ratio Association With Mortality in Patients on Maintenance Peritoneal Dialysis

Abstract: The cardiothoracic ratio (CTR) indicates the left ventricular size; however, the significance of the CTR in patients on maintenance peritoneal dialysis (PD) remains unclear. In this study, 335 PD patients were enrolled and demographic, biochemical, co-morbidity, and dialysis-related data were obtained. The factors determining CTR were further analyzed. All patients were followed up for two years to investigate the mortality risks. We defined a normal CTR as less than the mean CTR value, mild cardiomegaly as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 29 publications
3
22
0
Order By: Relevance
“…To our knowledge, there is no article on the influence of anemia on the CTR in nondialyzed ESKD patients. A recent report has shown that the Hb level is inversely associated with the CTR independent of confoundable variables in chronic peritoneal dialysis patients [18]. Our study has confirmed the same finding at the initiation of the dialysis, which may result from the management of anemia in the predialytic phase of the CKD course.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…To our knowledge, there is no article on the influence of anemia on the CTR in nondialyzed ESKD patients. A recent report has shown that the Hb level is inversely associated with the CTR independent of confoundable variables in chronic peritoneal dialysis patients [18]. Our study has confirmed the same finding at the initiation of the dialysis, which may result from the management of anemia in the predialytic phase of the CKD course.…”
Section: Discussionsupporting
confidence: 80%
“…The CTR negatively correlates with cardiac systolic dysfunction in patients with congestive heart failure [14]. A CTR >50% is associated with a poorer prognosis in community-dwelling elderly populations aged nearly 80 years [15] as well as in patients with congestive heart failure [16] and in those on dialysis [17,18]. Therefore, CTR would be an easier way to determine the status of cardiac remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…Studies carried out on human beings have shown a significant association between CTR, malnutrition and anemia, which are conditions that can lead to alterations in normal heart sounds under auscultation. 6 Furthermore, the CTR was a predictor of 13% mortality in patients with heart disease of any nature. 12 …”
Section: Discussionmentioning
confidence: 99%
“…The CTR was calculated as the ratio of the maximum transverse cardiac diameter in millimeters to the maximum thoracic diameter in millimeters. We defined a normal CTR value as less than 0.5 [29,30]. …”
Section: Methodsmentioning
confidence: 99%
“…However, it was shown that inflammation predicts future increase in BP, suggesting that increased inflammatory state may precede the increase in BP [29]. Assessment of these conditions and constant research on new serum blood markers and instrumental parameters in patients with ESRD appear mandatory to reduce the high cardiovascular morbidity and mortality [30,31]. …”
Section: Introductionmentioning
confidence: 99%